Influence of Teachers’ Religion and Gender on their Perception of the Usefulness of Family Planning in Ilorin West Local Government Area - Olushola, Iyekolo Alexander (Journal of Education and Learning (EduLearn), 2021)
This research works focused on the perception of teachers on family planning as influence by religion and gender in Ilorin West Local Government Area of Kwara State Family Planning is a means of controlling birth, it often helps in checking population growth to improve the welfare and standard of living of people in the country. Also, it is used to improve maternal and child health. The research was carried out by sampling 150 teachers from 15 schools. Data was gathered using a researcher-designed questionnaire titled Teachers Perception on Family planning as Influenced by Religion. Data collected were analyzed using simple percentage and frequency count for the demographic data of the respondents, the research questions were answered using mean and percentage statistical tools while the two hypotheses were analyzed using independent T-test at 0.05 level of significance. The result of the findings explained that teachers have a positive perception of family planning because 71.3% perceived it to be good also concluded that there was no significant difference in the perception of teachers based on religion and gender. It was recommended among others that religious leaders should encourage their followers to see family planning as beneficial to the betterment of the Nigerian family system